Wireless Network Analysis with Bandwidth Settings in MAN 3 Jakarta Using Cisco Packet Tracer - Willis Puspita Sari (LPPM Politeknik Aceh Selatan, 2024)
Dependence on wireless networks is increasing along with the development of information and communication technology. Schools are also increasingly adopting wireless network infrastructure to support teaching and learning activities and school administration. This research aims to analyze the wireless network at MAN 3 Jakarta with a focus on bandwidth management using Cisco Packet Tracer software. The methods used include modeling the MAN 3 Jakarta network using Cisco Packet Tracer, configuring wireless network devices such as routers and access points, as well as adjusting bandwidth to optimize network performance. Efficient use of bandwidth in wireless networks is important to ensure smooth and quality access for users. The result of this research is a better understanding of how bandwidth configuration can affect wireless network performance in school environments. By utilizing Cisco Packet Tracer as a simulation tool, users can conduct experiments and gain valuable insight into wireless network management. This research contributes to the development of network infrastructure at MAN 3 Jakarta or similar educational institutions by providing a more in-depth view of bandwidth management in the context of wireless networks.